Computational analysis of EMHD nanofluid flow over a thermally conductive surface: Enhancing heat transfer for industrial applications - Faiza Zahid; Muhammad Bilal Riaz (International Journal of Thermofluids)
This study endeavors to delve into the intricate interplay between Arrhenius activation energy and variable thermal conductivity within the context of electromagnetohydrodynamic fluid dynamics across an elongated sheet that radiates irregularly situated within a permeable material. The principal concern is to elucidate the nuanced effects on fluid motion of varying EMHD, particularly emphasizing synergistic influence of electric and magnetic fields, which can engender potent Lorentz forces with promising implications for industrial applications. The investigation holds particular relevance for sectors such as industrial, petroleum and gas, and chemical production, where amalgamation of electric and magnetic fields can yield advantageous outcomes. The problem under scrutiny yields a non-similar solution necessitating the transformation of governing partial differential equations into ordinary differential equations by the use of similarity variables. The complex capabilities of MATLAB, the programming bvp4c are used to get the numerical approximation. Through comprehensive graphical analyses, the study elucidates the influence of diverse parameters on microorganisms, velocity, concentration, and temperature profiles. The skin friction coefficient increments for surged values of permeability (Kp) and magnetic parameters (M). Increments in Brownian motion cause the local Sherwood number to dwindle. With an increase in the Peclet number, the density of motile microorganisms is decreasing. Furthermore, the current findings demonstrate commendable agreement with existing literature in specific instances, thereby validating the robustness of the approach and enhancing its credibility within the scientific community.